2007
DOI: 10.1007/s10350-007-9015-4
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Transanal Advancement Flap Repair: Impact on the Overall Healing Rate of High Transsphincteric Fistulas and on Fecal Continence

Abstract: PURPOSE: Transanal advancement flap repair (TAFR) has been advocated as the treatment of choice for transsphincteric fistulas passing through the upper or middle third of the external anal sphincter. It is not clear whether previous attempts at repair adversely affect the outcome of TAFR. The purpose of the present study was to evaluate the success rate of a repeat TAFR and to assess the impact of such a second procedure on the overall healing rate of high transsphincteric fistulas and on fecal continence. MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 18 publications
3
28
1
2
Order By: Relevance
“…In general, recurrence rates range from 13% to 56%. [81][82][83] The addition of fibrin glue to obliterate the tract has failed to improve success rates. 81,84 Factors associated with failed repair include radiation, underlying Crohn's disease, active proctitis, rectovaginal fistula, malignancy, and number of prior attempted repairs.…”
Section: Endoanal Advancement Flaps May Be Used For Treatment Of Compmentioning
confidence: 99%
“…In general, recurrence rates range from 13% to 56%. [81][82][83] The addition of fibrin glue to obliterate the tract has failed to improve success rates. 81,84 Factors associated with failed repair include radiation, underlying Crohn's disease, active proctitis, rectovaginal fistula, malignancy, and number of prior attempted repairs.…”
Section: Endoanal Advancement Flaps May Be Used For Treatment Of Compmentioning
confidence: 99%
“…Published results vary with respect to success of treatment, recurrence, technique used, patient cohort and length of follow-up. 6,[12][13][14][15][17][18][19] Prognosis is also affected by the complexity of the fistula and any secondary underlying disease that can affect fistula healing. However, treatment is considered successful and complete when the patient is free from fistula, has maintained continence and the fistula does not recur.…”
Section: Introductionmentioning
confidence: 99%
“…Encouraging fi ndings regarding continence have been found by a number of studies, which have found no change in continence after fl ap [ 46 , 47 ] or only transient changes in continence [ 15 ]. Similarly, when the Rockwood Fecal Incontinence Severity Index was measured preoperatively and postoperatively after initial and even repeat fl aps, no change in scores was found [ 18 ]. Some studies even report improved continence after fl ap, perhaps because there is no longer drainage through the fi stula tract [ 5 , 35 ].…”
Section: Clinical Resultsmentioning
confidence: 95%
“…Mitalas et al performed a second advancement fl ap in 26 patients with transsphincteric cryptoglandular fi stulas who had recurrence after an initial rectal advancement fl ap [ 18 ]. The healing rate after the second fl ap was 69 %.…”
Section: Healing Rates After Repeat Flapmentioning
confidence: 95%